Black soldier fly farming for feed and biofertilizer: a practical guide - Adamtey, Noah; Badu, E.; Ayimba, N.; Kimathi, F.; Gebrezgabher, Solomie A. (International Water Management Institute, 2024)
The aim of this guide is to facilitate the utilization of Black Soldier Fly (BSF) as an alternative protein and fertilizer source, contributing to employment generation and poverty reduction. It is designed to support farmers, small and medium enterprises (SMEs), Extension Agents, and other stakeholders in acquiring the necessary knowledge and skills to engage in BSF farming as a viable business opportunity. Serving as an all-encompassing guide, it systematically outlines the ‘how’ and ‘why’ behind each stage of the BSF production cycle, starting from initial startup (point zero) to the successful harvesting phase. The manual also delves into the science of BSF farming, elucidates the steps for establishment, covers best practices, and provides insights into potential challenges within the production chain, along with strategies for ensuring the sustainability of the BSF enterprise.